Theory of Planned Behavior: Intention to Quit Smoking at Universitas Negeri Malang during Pandemic Covid-19 - Windi Chusniah Rachmawati; Yunita, Anis; Endang Sri Redjeki (Universitas Airlangga, 2023)
Background: Smoking has become a lifestyle. Smokers are dominated by teenagers, including college students. Smoke from cigarettes clearly poses a danger to the body's health and the environment, especially during the COVID-19 pandemic. During the pandemic, college students spend more time at home which can increase smoking behavior too. Aims: The purpose of this study is to analyze the description of the intention to quit smoking at the State University of Malang during COVID-19 based on the Theory of Planned Behavior (TPB). Methods: This research is a type of quantitative analysis using primary data. The instrument used is a questionnaire which is filled out independently by the respondent. Data collection was done online for 100 students of the State University of Malang. The statistical test used in the analysis is the Chi-square test and Regression Logistic. Results: Variables related to the intention to quit smoking were attitude (sig=0.03 < α=0.05) and behavioral control (sig=0.00 < α=0.05), while the subjective norm variable had no relationship with intention, quit smoking (sig=0.077 > α=0.05). Behavioral control has a significant effect on the intention to stop smoking (sig = 0.00 > α=0.05). Conclusion: There is a relationship between attitude and behavioral control with students' intention to quit smoking. Only behavioral control affects the intention to quit smoking, so it is necessary to strengthen this variable to increase the intention of students at the State University of Malang to quit smoking and as an effort at tobacco control among adolescents.